PENANGANAN PASCA PANEN SAYUR BROKOLI DI KABUPATEN ENREKANG - Abriana, Andi; Laga, Suriana (Jurnal Ilmiah Ecosystem, 2019)
Broccoli vegetables are one of the vegetables included in the cabbage tribe produced in Baroko Subdistrict, Enrekang Regency, which has high economic value with good quality production, so post-harvest handling needs to be done so that it remains qualified according to consumer demand. This study aims to determine how to handle post-harvest broccoli vegetables and the quality of broccoli in the garden and after transportation. The usefulness of this study is that it can provide a deeper understanding of the handling of post-harvest broccoli vegetables. Farmers can also use the results of this study to add insight into the post-harvest process, and as information material for broccoli vegetable farmers and subsequent research. The postharvest handling stage of broccoli consists of harvesting, collecting, sorting, cleaning, grouping, packaging, and transportation; the color of broccoli vegetables in the garden remains greenish and at the supermarket broccoli changes color because of the flowers from broccoli having black spots; and the diameter of 10-12 cm broccoli vegetables transported to supermarkets (Makassar), while broccoli vegetables with diameters below 10-12 cm are sold in traditional markets.